Prescriptive appropriateness in primary cardiovascular prevention: data from our hospital. (3rd October 2022) - Maloberti, A; Ceruti, D; Gualini, E; Colombo, V; Giani, V; Milani, M; Sun, J; Alloni, M; Giannattasio, C
Abstract: Background: The main cause of waste of health resources is represented by overuse of diagnostic and therapeutic procedures. Given its high prevalence and the importance of identifying hypertensive-mediated organ damage, management of patients with arterial hypertension can lead to a lack of appropriateness. The aim of this study was to evaluate the prescriptive appropriateness of non-invasive diagnostic tests (Echocardiography, Carotid ultrasound, ECG exercise testing, 24h Ambulatory blood pressure monitoring) in outpatients referring to an ambulatory of primary cardiovascular prevention. Methods: 559 specialistic ambulatory visits were retrospectively analysed and appropriateness of every prescription was evaluated. An integration of different Italian and European guidelines was used to define appropriateness. Moreover, we evaluated the correlation between prescriptions, appropriateness and clinical characteristics of the population. Results: During the 559 ambulatory visits analysed, 449 prescriptions were made, including 198 echocardiographies, 148 carotid ultrasound, 85 24h ABPM and 18 ECG exercise testing. The global percentage of appropriate prescriptions was 40.3%. Focusing on each test, appropriateness rate was 49.4% in 24h ABPM, 43.9% in echocardiography, 38.9% in ECG exercise testing and 30.4% in carotid ultrasound. A significant correlation was identified between the age and cardiovascular risk category of patients and the appropriateness of echocardiography, 24h ABPM and carotid ultrasound, and a correlation between appropriateness of echocardiography and the duration of hypertension and the presence of valvular heart disease. Conclusions: Our study shows a relevant percentage of inappropriate prescriptions of non-invasive cardiologic exams; moreover, there might be a greater lack of appropriateness in young and low risk patients. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Niguarda Hospital, Milan, Italy